Coomassie Stainable Particles (CSP): Protein Containing Exopolymer Particles in the Ocean - Thornton, Daniel C. O. (Frontiers in Marine Science, 2018)
Exopolymer particles play a significant role in biogeochemical processes in the ocean. Coomassie stainable particles (CSP) are a class of gel-like exopolymer particles that contain protein. CSP are also abundant and ubiquitous in the global ocean, from the sea surface microlayer (SML) to depths in excess of 4,000 m. A synthesis of data from the literature estimates a median CSP concentration of 58 mm2 L-1, with a median particle abundance of 21 x 106 particles L-1. CSP are also abundant in cultures of diatoms, cyanobacteria, and heterotrophic bacteria, indicating that microorganisms are a significant source. Limited data suggest that CSP are more labile and less sticky than transparent exopolymer particles (TEP). CSP are a component of primary organic aerosol and are injected into the atmosphere by bubble bursting. However, it is not known whether CSP contribute to cloud formation by acting as cloud condensation nuclei (CCN) or ice nucleating particles (INP). Better conceptual models of the factors affecting CSP production are needed. These should integrate the physiological ecology of microorganisms producing or degrading CSP with abiotic processes, such as particle aggregation. Whether CSP is a conceptually, rather than operationally, useful definition depends on whether CSP have unique and measurable properties that distinguish them from the bulk dissolved organic matter (DOM) and particulate organic matter (POM) pools, and TEP. A research priority is the development of methods to quantify CSP in terms of biogeochemically significant elements, namely carbon and nitrogen. It is only through quantitative methods that the significance of CSP in processes, such as the biological carbon pump and marine aerosol dynamics, can be determined.